Precarious employment and gender-based violence against migrant women: A scoping review mapping the intersections - Cyndirela Chadambuka; Prossy Kiddu Namyalo; Rhea Raghunauth; Navya Arora; Fiona Kouyoumdjian; Beverley M. Essue (PLoS ONE, 2025)
The risk of gender-based violence (GBV) against migrant women is largely exacerbated by precarious employment opportunities available to them as they go through the resettlement process. Despite the risk that the connection of precarious employment and GBV pose to migrant women’s health and wellbeing, critical gaps exist in literature. Our scoping review sought to identify and synthesize evidence on the interconnectedness of GBV and precarious employment among migrant women. Six electronic databases were searched for empirical literature and two reviewers independently conducted title/abstract and full text screening of studies that met the inclusion criteria. Data synthesis was guided by the intersectionality theory and the Feminist Political Economy framework. 50 articles met the criteria for inclusion in this review. Our findings reveal that precarious employment plays both a catalytic and consequential role in GBV. Findings highlighted how post-migration shifts in gender roles, schedule unpredictability leading to work-life imbalance, and debt bondage trap migrant women in cycles of exploitation and abuse. Few studies highlighted how human trafficking is intertwined with precarious labor markets, where the exploitation and abuse of migrant women mirror the characteristics of human trafficking. This review underscores the urgent need for integrated policy responses that are not only focused on individual supports but also address the structural drivers or labor precarity and protect migrant women from GBV and human trafficking. By applying an intersectional lens, policies and intervention programs can tackle systemic oppression across economic, and social systems essential in reducing exploitation and abuse to advance migrant women’s wellbeing.